Analisis Dampak Perkembangan Teknologi Terhadap Model Bisnis dan Pemasaran di ISC Komputer Kutowinangun Kebumen - Niken Lestari; Muhammad Fajrul Hakim; Eka Arilia Nandasari (Jurnal Perilaku dan Strategi Bisnis, 2024)
Technological developments have changed many sectors, one of which is in the business world. Business actors are required to continue to be updated on technological developments that are increasingly rapidly increasing day by day. This demand is also in line with consumer behavior that changes with the development of the technology, where there are many features that make it easier for consumers to get what they want, and vice versa, technology also makes it easier for business people to run their business. Talking about impact, it is not only convenience or positive things that are presented by technological developments, but there are always weaknesses/negative sides as a comparison and consequence of a change. Therefore, this research is important to do to analyze and find out the impact of increasingly rapid technology on business which will later become a business evaluation in the future. Moreover, the times are increasingly sophisticated and must be balanced with an understanding of technology in order to facilitate business. This study aims to determine the impact of technological developments on business and marketing models at ISC Komputer Kebumen. This study uses a qualitative approach with data collection techniques using interviews, observation and documentation and the research location is at ISC Komputer Kutowinangun Kebumen. The results of this study indicate that technological developments affect the business at ISC Komputer starting from its changing business model by utilizing technological developments. Then in terms of marketing, technological developments affect ISC Komputer in terms of product strategy, location and distribution strategy, price strategy, and promotion strategy. Technological developments have a positive impact as well as a negative impact on ISC Komputer where the positive impact of ISC Komputer can expand its reach, while the negative impact of ISC Komputer is that it is more difficult to get big profits and competition is getting tougher.